Reflections on Governance and Development in Nigeria - Adamolekun, Ladipo (Taylor & Francis, 2026)
In this book, published for the first time with Routledge in 2025 and including some previously unpublished papers, the renowned professor of public administration Ladipo Adamolekun argues powerfully that only a devolved Nigerian federation can become a well-performing state that is capable of achieving good development performance. He discusses and ranks seven governance issues which include electoral legitimacy, rule of law, and civil liberties as well as development-oriented leadership, administrative competence, accountability and transparency (including anti-corruption). Professor Adamolekun has based his rankings on over six decades of the study and observation of the differing dimensions of the issues and suggests that the federal government and each of the subnational governments in a devolved federation should be responsible for sequencing the necessary reforms, taking into account the strengths and weaknesses of their respective governance structures and processes. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC BY-NC-ND)] 4.0 license.